A Framework for Aiding the Translation of Scientific Evidence into Policy: The Experience of a Hospital-Based Technology Assessment Unit. (24th April 2019) - Almeida, Nisha D.; Mines, Lorraine; Nicolau, Ioana; Sinclair, Alison; Forero, David Felipe; Brophy, James M.; Mayo, Nancy; Dendukuri, Nandini
Abstract: Objectives: Very few practical frameworks exist to guide the formulation of recommendations at hospital-based health technology assessment (HTA) units. The objectives of our study were: (i) to identify decision criteria specific to the context of hospital-based health technologies and interventions, (ii) to estimate the extent to which the expert community agrees on the importance of the identified criteria, (iii) to incorporate the identified criteria into a decision-aid tool, and (iv) to illustrate the application of a prototype decision-aid tool. Methods: Relevant decision criteria were identified using existing frameworks for HTA recommendations, our past experience, a literature search, and feedback from a survey of diverse stakeholders. Results: Based on the survey results, twenty-three decision criteria were incorporated into the final framework. We defined an approach that eschewed a scoring system, but instead relied on a visual means for arriving at a final recommendation, by juxtaposing the importance rating for each criterion against the results of the health technology assessment. For a technology to be approved, a majority of criteria considered important should also have received favorable findings. Conclusions: We created a simple and practical decision-aid tool that incorporates all decision criteria relevant to a hospital-based HTA unit. With its ease of use and accessibility, our tool renders the subjective decision-making process more structured and transparent.